(Un-)scientifically spun: narratives, belief updating, and pro-environmental behavior - Banerjee, Anwesha; Momsen, Katharina (Environmental and resource economics, 2025)
In an experiment conducted with 2346 US residents, we examine the effect of content (positive/ negative/ inconclusive) and style (scientific/unscientific) of narratives about CO2 emissions on belief updating and pro-environmental behavior. We use the Work for Environmental Protection Task (WEPT) by Lange and Dewitte (Behave Res Methods 54:133-145, 2022) as a proxy for pro-environmental behavior. Narratives are constructed using the natural language processing chatbot ChatGPT. We find that negative narratives significantly increase concern regarding CO2 emissions, while positive narratives significantly decrease concern, with the latter effect being significantly larger in terms of absolute value. For inconclusive narratives, the effect on beliefs depends on prior beliefs: Subjects with low prior beliefs increase their concern, whereas subjects with high prior beliefs decrease their concern. Moreover, we find that the unscientific style has a stronger effect on belief updating than the scientific style. Neither content nor style affects pro-environmental behavior significantly.
Gesehen am 20.02.2026